2018
DOI: 10.1007/s40710-018-0310-y
|View full text |Cite|
|
Sign up to set email alerts
|

Unit Energy Consumption as Benchmark to Select Energy Positive Retrofitting Strategies for Finnish Wastewater Treatment Plants (WWTPs): a Case Study of Mikkeli WWTP

Abstract: Retrofitting municipal wastewater treatment plants (WWTPs) to energy positive is a major challenge faced by many water utilities. Selection of innovative technologies to achieve retrofitting goals is critical for capital improvement programs in WWTPs. This paper aims to provide a statistical analysis method of unit energy consumption in conventional Finnish WWTPs, presenting Mikkeli WWTP as a case study. The average energy consumption at Finnish WWTPs was quantified as a mean of 0.49 kWh/m 3 with a standard de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…The unit energy consumption of WWTPs with the same process and scale increases with the improvement of effluent quality, which is consistent with conclusion of Han [34]. Some researchers hold the opinion that the expansion of the WWTP scale helps to reduce unit energy consumption [35,36]. However, Han et al found that unit energy consumption would have a reverse increase if scale exceeded the boundary [28].…”
Section: Influencing Factorssupporting
confidence: 81%
“…The unit energy consumption of WWTPs with the same process and scale increases with the improvement of effluent quality, which is consistent with conclusion of Han [34]. Some researchers hold the opinion that the expansion of the WWTP scale helps to reduce unit energy consumption [35,36]. However, Han et al found that unit energy consumption would have a reverse increase if scale exceeded the boundary [28].…”
Section: Influencing Factorssupporting
confidence: 81%
“…The daily energy demand was 14.4 Wh (51.8 kJ) or 0.20 kWh/m 3 treated which could easily be supplied by a small solar panel. For a sanitation system comprising an anaerobic digester and the filters as described herein, the aeration pump would be the only energy demand which is much lower than that of traditional wastewater treatment plants, which were estimated at 0.49 kWh/m 3 ( Gurung et al., 2018 ). No exogenous electron donors were supplied to the denitrification filters as the bamboo chips provided enough reducing equivalents and did not show any indication of requiring replacement.…”
Section: Discussionmentioning
confidence: 99%
“…The potential reduction in the amount of wastewater to be treated by the WWTP results in considerable energy savings. The average energy consumption at Scandinavian wastewater treatment plants is quantified as an average of 0.49 kWh/m 3 with a standard deviation of 0.197, 33 and the density of wastewater is between 998 and 1001 kg/m 3 34 . The comparative analysis between systems with and without FGQ shows a potential reduction of 73 tons of wastewater per day to the WWTP that may results in potential annual energy savings of about 13.1 MWh based on the reference CHP plant capacity.…”
Section: Resultsmentioning
confidence: 99%